Teachers as leaders - Ravit, Amir; Keren, Grinberg (IJRDO - Journal of Applied Management Science, 2016)
Fact that it is a moral issue. Teachers have potential ability to affect mainly the differentsystems within the school and beyond. Teacher leadership is reflected in actions whichsteppes not only the class, or the school environment, but to the community as a whole. Theteacher, as an agent of socialization, are actively involved in the creation andinstitutionalization of new systems of behaviors and values chain designed to improve thequality of life of the community in the long run. The teacher is the person who may bringsystemic change and for improving the quality of information and what they are comfortable.functioning in school (Bugler, 2000)assumptions related to the functioning of principals and teachers in the school. They mustrecognize that the manager is not the only source of leadership in the teaching educationalinstitution, but each member of staff can assume leadership responsibilities and should dobetween its units, leaves teachers considerable leeway to influence school performance. If .sothe school principal creates an atmosphere of cooperation and encourage the staff to take the.initiative and act, created fertile ground for teacher leadership can come from it